A seletividade alimentar e o setting analítico: um estudo de caso sob a ótica da Teoria do Amadurecimento Emocional de Donald Woods Winnicott - Prado, Eduardo Fraga de Almeida (2013)
Feeding disorders is a term that comprehends a wide range of symptoms or complaints that include refusal and food selectivity. It has a multifactorial etiology and it involves biological, genetic, psychological, sociocultural and family-related factors. The consideration of the mother as being co-responsible for the child s eating habits is consensual, although it is impossible to identify where the difficulties arise in causal terms, whether from the mother s feelings or the child s behavior. The literature on the subject emphasizes childhood as the period par excellence for both the etiology and the extinction of the condition, often interpreting it as a "natural" stage in terms of development. The arising or persistency of food selectivity in adults is a less common phenomenon, normally classified as an unspecified eating disorder and, at first, it lacks further studies. With the assistance of Donald Woods Winnicott s Theory of Personal Development, this research aims at contributing to the understanding of the etiology and the possible therapeutic management of adult patients with food selectivity. In order to accomplish such task, we covered Winnicott's work with an exploratory approach, focusing on the items that could contribute to the subject of this study. Therefore, it was possible to approach the food selectivity phenomenon based on at least two assumptions: (1) as a defense mechanism of obsessive nature, (2) as a defense mechanism to try to deal with a persecutory anxiety. Lastly, in spite of the hypotheses explored in the survey, the conclusion points to the need for further studies in search of psychodynamic understanding of the food selectivity phenomenon